Pengaturan Lembaga Pemerintah Penyelenggara Penanaman Modal dalam Penyelenggaraan Urusan Penanaman Modal di Indonesia - Erlangga Erlangga (UNES Law Review, 2023)
Investment or investment activities are defined as activities carried out by individuals and legal entities seeking to increase and maintain the value of their capital, both in the form of cash, immovable assets, intellectual property rights, and expertise. There is a legal basis in Capital Investment and several main provisions that become a reference for carrying out its activities, such as institutional aspects, employment, legal protection aspects and others. This is where it seems very important to understand the main provisions in the field of investment, so that it is clearer in carrying out the related rules, in order to carry out investment properly. The research method in this study uses literature studies that are processed and analyzed through a qualitative approach. This research is qualitative research. Regulations for the implementation of investment licensing affairs in Indonesia are regulated in Law Number 25 of 2007 concerning Capital Investment and several implementing regulations. The duties and functions of investment organizing government institutions in the main provisions in the field of investment have the characteristics of investment licensing carried out through one-stop integrated services, namely the implementation of a permit and non-licensing that receives delegation from institutions or agencies that have licensing and non-licensing authority whose management process starts from the application stage to the stage of issuance of documents carried out in one place.